2022
DOI: 10.1021/acsnano.1c10430
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of Branching Out: Linear versus Branched Alkylthiols Ligands on CdSe Nanocrystals

Abstract: Surface ligands of semiconductor nanocrystals (NCs) play key roles in determining their colloidal stability and physicochemical properties and are thus enablers also for the NCs flexible manipulation toward numerous applications. Attention is usually paid to the ligand binding group, while the impact of the ligand chain backbone structure is less discussed. Using isothermal titration calorimetry (ITC), we studied the effect of structural changes in the ligand chain on the thermodynamics of the exchange reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 97 publications
(178 reference statements)
0
39
0
Order By: Relevance
“…Previous studies of other systems have also shown lower reactivity for surfaces protected by branched alkyl monolayers compared to linear ones. 48,66 For the secondary alkyl ZDDPs at 80 °C and 1000 N, the reactivity increases in the order: oct-2-yl < 4-methylpent-2-yl < but-2-yl. The trend is similar to the primary ZDDPs in that the secondary ZDDPs with longer alkyl chains give slower tribofilm formation rates, which can again be attributed to the formation of more densely packed SAMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of other systems have also shown lower reactivity for surfaces protected by branched alkyl monolayers compared to linear ones. 48,66 For the secondary alkyl ZDDPs at 80 °C and 1000 N, the reactivity increases in the order: oct-2-yl < 4-methylpent-2-yl < but-2-yl. The trend is similar to the primary ZDDPs in that the secondary ZDDPs with longer alkyl chains give slower tribofilm formation rates, which can again be attributed to the formation of more densely packed SAMs.…”
Section: Resultsmentioning
confidence: 99%
“…47 Therefore, for most of the ZDDPs studied here, variation in the adsorption behavior is not expected to significantly affect the tribofilm formation rate on steel. However, for the ZDDPs containing longer branches 48 (2-ethylhexyl) and particularly the bulky cycloaliphatic substituents 49 (2-cyclohexylethyl), SAMs with lower packing densities are expected to form, which may affect their mechanochemical response.…”
Section: Methodsmentioning
confidence: 99%
“…For the primary ZDDPs with C8 alkyl groups, the tribofilm growth rate increases in the order: 2-cyclohexylethyl < 2ethylhexyl < oct-1-yl. This suggests that the increased steric bulk has a larger effect on the rate than the lower packing density expected for the ethyl-branched 45 and particularly cyclohexylcontaining 46 ZDDPs compared to the linear one. Previous studies of other systems have also shown lower reactivity for surfaces protected by branched alkyl monolayers compared to linear ones.…”
Section: Resultsmentioning
confidence: 94%
“…Previous studies of other systems have also shown lower reactivity for surfaces protected by branched alkyl monolayers compared to linear ones. 45,61 For the secondary alkyl ZDDPs at 80 °C and 1000 N, the reactivity increases in the order: oct-2-yl < 4-methylpent-2-yl < but-2-yl. The trend is similar to the primary ZDDPs in that the secondary ZDDPs with longer alkyl chains give slower tribofilm formation rates, which can again be attributed to the formation of more densely packed SAMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation